Employing a Database for the Morpho-Phonological Study of Ckunsa - Llanquiman Iturrieta, Eduardo Alejandro (2025)
This study focuses on the preservation and revitalization of Ckunza, the language of the Atacameño-Lickanantay Indigenous people. Based on the intersection between technology and language revitalization, it proposes the dissemination of a morphophonological linguistic database. The construction of the corpus was carried out in three phases: the compilation and analysis of a bibliographic list, the development of a lexicon containing Ckunza words extracted from that analysis and the morphophonological breakdown of each of those lexical forms. Potential lines of analysis include the frequency of graphemes and phonemes, the identification of syllabic patterns, the evaluation of morphemic consistency, and the detection of lexical borrowings. Possible outputs from these linguistic resources include digital applications, educational materials, and more effective translations. This study contributes to the promotion of linguistic and cultural diversity while strengthening the connection of Indigenous communities with their language using information and communication technologies. In particular, the digitalization of studies on Ckunza aims to advance linguistic justice for the Atacameño people.